Effect of Some Chemical and Biological Fertilizers on Productivity of Medicinal Flax ( Linum usitatissimum ) Plant - Khourang, Mahmoud; Ghasem Hossein, Talaei; Mehdi, Rezaei; Brumand, Parisa (Pharmacognosy Communications)
A fi eld experiment was carried out at the Experimental Station, Faculty of Agriculture, Trbiat Modares University, during spring season of 2009-2010, to study the effect of some chemical and biological fertilizers containing macro nutrients (i.e 100 kg/ha Urea as the source of N, 100 kg/ha calcium super phosphate as the source of P, 150 kg/ha Potassium sulphate as the source of K and 150 kg/ha N.P.K (10–15–10) fertilizer as the source of macro complete fertilizer, combination of 50 kg/ha + 50 ton/ha animal manure and 100 ton/ha animal manure) on yield and its components of medicinal fl ax plant. The earliest and latest fl owering date of plants were achieved by applying N.P.K fertilizer and 100 ton/ha animal manure, respectively. The highest plant height in the full fl owering stage was obtained by application of 100 ton/ha animal manure. Seeding date of plants was also signifi cantly affected by applied fertilizers; 100 ton/ha animal manure and N.P.K treatment caused the latest and the earliest seeding date of plants, respectively. The lowest seed index was obtained in control treatment, whereas N.P.K fertilizer caused the highest 1000-seed weight. Seed yield, seed oil percentage and oil yield reached the highest values by adding 150 kg/ha potassium sulphate. Meanwhile oil compositions of the extracted oils were signifi cantly different because of applying different fertilizers, and linoleic acid had the highest amount in all of the tested samples. Ultimately, 100 ton/ha animal manure showed its leading impact on the protein content of seeds.
Keywords: Fertilizer; Flax; Linum Usitatissimum L .; Medicinal Plants